ESTUDIO AL MICROSCOPIO ELECTRONICO DE BARRIDO (MEB) DE DOS CYCADOPSIDAS FOSILES DE ARGENTINA. PSEUDOCTENIS DENTATA ARCHANGELSKY Y BALDONI 1972 Y SUERIA RECTINERVIS MENENDEZ 1965 (Ameghiniana, 2013)
The study with Scanning Electron Microscope of Pseudoctenis dentata Archangelsky & Baldoni 1972 and Sueria rectinervis Menéndez 1965 is presented. The specimens were found in the Baqueró Formation (Early Cretaceous), Santa Cruz province, Argentina. Both possess sunken stomata located under a cycle of subsidiary cells that are characterized by having a cutine ring. The cuticle ornamentation is composed of striations and folds, as in other fossil Cycads. While Pseudoctemis dentata has a pinnate leaf Sueria combines a taeniopteridean shape of the leaf with special cuticular characters like perforations in the anticlinal walls and secretory idioblasts, suggesting that it is a well established genus.